Comparing the Impact of Non-Cognitive Skills in STEM and Non-STEM Contexts in Kazakh Secondary Education - Gulbakhyt Sultanova; Nurym Shora (MDPI AG, 2024)
The role of non-cognitive skills in academic achievement has garnered increasing attention in educational research. This study explores the impact of non-cognitive skills on academic achievement in STEM and non-STEM subjects in secondary education. Survey data from 795 teachers and 12,965 students across 20 STEM schools in Kazakhstan were analyzed to examine the impact of 26 non-cognitive skills on performance in math, physics, first language, and history. Regression and mediation analyses were conducted to investigate how students' self-assessment of non-cognitive skills directly affects academic achievement and how these effects are mediated by teachers' assessments. The findings indicate that non-cognitive skills exhibit varying direct and total effects, with mediated effects showing greater consistency across different subjects. In math and physics, information processing skill and grit show the strongest direct and total effects on academic achievement. In first language and history, responsibility management and teamwork skill are most influential. Except for capacity for optimism and growth mindset, all skills demonstrated mediated effects across the four subjects. This research informs curriculum development and equitable policies by showing how non-cognitive skills impact academic performance across subjects. It studies the case of Kazakhstan, adding to global education discourse and offering valuable insights for enhancing STEM education.